Development of an Internet of Things (IoT)-Based Plant Monitoring System Using a Capacitive Soil Moisture Sensor, ESP32, Firebase Realtime Database, and a Mobile Application - Nur Haliza Daulay; Edi Irawan Siregar; Wahyudi Bayu Pamungkas; Yeremia Herlanggi Wijaya (Pascal: Journal of Computer Science and Informatics, 2026)
Soil moisture is one of the most important parameters affecting plant growth because it is directly related to water availability in the growing medium. Conventional soil moisture monitoring is generally performed manually, relying on visual observation, lacking periodic data recording, and making remote monitoring difficult. This study aims to design, implement, and evaluate an Internet of Things (IoT)-based plant monitoring system using a capacitive soil moisture sensor, an ESP32 microcontroller, Firebase Realtime Database, and an Android mobile application. The study employed an engineering research approach using the Prototype development model, consisting of requirements analysis, system design, prototype development, hardware and software integration, and system testing. The prototype was evaluated using 10 chili pepper pots over a period of 14 days with a data acquisition interval of 30 minutes. The results demonstrate that the proposed system successfully measures soil moisture, transmits data to Firebase in real time, and displays soil conditions through the mobile application with an average response time of 2.6 seconds. Accuracy evaluation indicates that the capacitive soil moisture sensor provides a relatively low measurement error, making it suitable for small-scale plant monitoring applications. In addition to displaying soil moisture values, the system automatically classifies soil conditions into dry, normal, and wet categories, enabling users to determine appropriate irrigation schedules more easily. This study contributes a simple, low-cost, and user-friendly IoT-based plant monitoring system that supports the implementation of smart farming for household gardening, educational purposes, and small-scale agricultural applications.